Research challenges to improve the management and conservation of subtropical reefs to tackle climate change threats - Beger, Maria; Babcock, Russ; Booth, David J.; Bucher, Daniel; Condie, Scott A.; Creese, Bob; Cvitanovic, Christopher; Dalton, Steve J.; Harrison, Peter; Hoey, Andrew; Jordan, Alan; Loder, Jennifer; et al. (Ecological management & restoration, 2011)
Summary This paper reports on a workshop conducted in Australia in 2010, entitled ‘Management, Conservation, and Scientific Challenges on Subtropical Reefs under Climate Change’. The workshop brought together 26 experts actively involved in the science and management of subtropical reefs. Its primary aim was to identify the areas of research that need to be most urgently addressed to improve the decision‐making framework for managers of subtropical reefs. The main findings of the workshop were a sustainable subtropical reefs declaration that highlights seven research priorities for subtropical reefs. These are to (i) conduct research and management activities across local government, state and bioregion borders; (ii) understand natural variability of environmental conditions; (iii) quantify socio‐economic factors and ecosystem services; (iv) benchmark cross‐realm connectivity; (v) know marine population connectivity; (vi) habitat mapping and ecological research; and (v) determine refugia. These findings are hoped to form a basis for focussing research efforts, leveraging funds and assisting managers with allocation of resources.